Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran Problem Solving Pada Materi Persamaan Linear Dua Variabel Pada Siswa Kelas X SMA Al-Khasanah Tidore Kepulauan - Hujairah Hi Muhammad (Peneliti.net, 2021)
The purpose of this study (i): To find out the implementation of problem solving learning on the material of linear equations of two variables for class X students of SMA Al-Khasanah City of Tidore Islands? (ii) To find out the magnitude of the increase in students' critical thinking skills through problem solving learning models on the material of linear equations of two variables in class X SMA Al-Khasanah City of Tidore Islands? This type of research is classroom action research (Class Room Action Research). The CAR design in this study uses the Kemmis and McTaggart model which includes four steps (steps), namely (1) action planning; (2) implementation of actions; (3) observation; and (4) reflection. This research was conducted in class X SMA Al-Khasanah Tidore Islands, which consisted of 16 students. Data collection techniques using observation, documentation, and test techniques. Quantitative data analysis techniques used descriptive statistical analysis. The results showed that students' critical thinking skills and learning outcomes increased from cycle I to cycle II. The percentage of achievement in the first cycle of students' critical thinking skills is a percentage of 68.75% which is in the critical category in the second cycle of students' critical thinking skills with a percentage of 93.75% increasing by 25%. Improved learning outcomes in the first cycle obtained data 9 students 56.25% completed learning and 7 students 43% had not finished learning with an average class of 62. Cycle II there were 15 students (93.75%) completed learning and 1 student (6.25 %) have not finished studying with an average value of 77.37. Based on these data, student learning outcomes using the problem solving model obtained an increase, from cycle I to cycle II (37.50%) with an average increase of 15.37.